Selection of non-Saccharomyces yeasts to be used in grape musts with high alcoholic potential: A strategy to obtain wine with reduced etanol content - Mestre Furlani, Maria Victoria (2017)
Ethanol content of wine has increased over the last decades as consequence of searching phenolic maturity, requiring increased grape maturity. This may result in the production of wines with excessive alcohol levels (sometimes more than 15% (v/v)), sluggish and stuck fermentations and excessive volatile acidity. Many strategies to reduce ethanol in wines are being studied, and microbial methods have some additional advantages. However, because of the broad intra- and interspecies variability, new selection criteria should be included. Therefore, the goal of the present work was to design and evaluate a simple and integral procedure for non-Saccharomyces yeast selection. This strategy allowed selection of yeasts that presented successful implantation in grape must with high alcohol potential and their use in co-cultures could reduce the ethanol in wines. A total of 114 native non-Saccharomyces yeasts were assayed to determine their respiratory, fermentative and physiological characteristics of enological interest. Hanseniaspora uvarum BHu9 and BHu11, H. osmophila BHo51, Starmerella bacillaris BSb55 and Candida membranaefaciens BCm71 were selected as candidates to design co-culture starters